A Constructivist Approach to Visualise Organisational Agility - Henning Bundtzen; Mark Heckmann; Gerriet Hinrichs (Business Ethics and Leadership)
The research question we would like to answer with this article is if agile related constructs or personal assessment criteria can be elicited from a personal construct system of employees and leaders by carrying out a repertory grid study in an organisation. The methodology of personal construct psychology was chosen to get an unbiased view of the corporate culture. In a plannable world an organisational structure with a hierarchy of executives and managers following a vertical top-down approach makes sense. A world that is volatile, uncertain, complex, and ambiguous (VUCA) requires a different model to organisational design. Horizontal integration that fosters involvement and empowerment has proven to be an agile response to this new environment. Consequently, agile management methods are a key instrument for an organisation to prepare for future challenges in a competitive industry. But how can an organisation assess its own agile status quo? This research uses personal construct psychology (PCP) to visualize the agility status of an organisation. A range of recent empirical and practical research articles were studied to filter the most relevant practices and critical factors of organisational agility. The findings are compared to a data basis generated by 61 repertory grid interviews carried out in a SME to evaluate whether personal construct theory is a suitable approach to assess the agility status of an organisation. The findings are visualised with a repertory grid software using Generalised Procrustes Analysis (GPA). This methodology creates a 3D visualisation of the agile assessment criteria derived from the interviews. By comparing the spatial distances between construct clusters and elements the researcher and reader able to assess whether an organisation has incorporated agile practices and traits or can further advance to react more agile and flexible to external forces. Repertory grid structured interviews based on PCP generate simultaneously quantitative and qualitative results. As these are compared to the literature-based findings, it reflects a triangulation research approach.